Efektivitas Edukasi dalam Peningkatan Pengetahuan Ibu Mengenai Akupresur untuk Mengatasi Mual Muntah - Dwi Yuniar Billy Canser; Siti Asyiyah; Masruroh (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Nausea and vomiting are often experienced by pregnant women in the first trimester. If left untreated, it can have dangerous consequences for both the mother and the fetus. Acupressure at the Pericardium 6 point is effective in reducing nausea and vomiting. The purpose of community service is to increase the knowledge of pregnant women regarding the benefits of P6 acupressure to overcome nausea and vomiting in pregnancy. The Community Service method will be implemented in 3 stages: The first stage is preparation by conducting a problem assessment and collaborating with partners. The second stage is conducting a pre-test to explore the level of knowledge of pregnant women, providing counseling on P6 acupressure to overcome nausea and vomiting and demonstrations. The third stage is conducting an evaluation by giving a post-test to pregnant women. From the results of the Community Service, it was found that this activity was attended by 10 pregnant women. The results showed that before the counseling, the majority of pregnant women had a poor knowledge category, namely 10 people (100%). After the counseling, the majority of pregnant women had a good knowledge category, namely 7 people (70%). In conclusion, there was an increase in the knowledge of pregnant women regarding the benefits of P6 acupressure to overcome nausea and vomiting. It is hoped that health workers will increase education for the public, especially pregnant women, regarding the use of acupressure as a non-pharmacologic method to reduce nausea and vomiting in pregnant women so that the well-being of the mother and fetus is improved.   Abstrak Mual muntah sering dialami ibu hamil pada kehamilan trimester I. Apabila tidak diatasi akan menimbulkan akibat yang membahayakan ibu dan janin. Akupresur pada titik P6 efektif dalam mengurangi mual muntah. Tujuan pengabdian masyarakat adalah untuk meningkatkan pengetahuan ibu hamil mengenai manfaat akupresur P6 untuk mengatasi mual muntah pada kehamilan. Metode Pengabdian Masyarakat telah dilaksanakan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan pengkajian permasalahan dan kerja sama dengan mitra. Tahap Kedua melakukan prestest untuk menggali tingkat pengetahuan ibu hamil, memberikan penyuluhan mengenai akupresur P6 untuk mengatasi mual muntah dan demonstrasi. Tahap Ketiga Melakukan evaluasi dengan cara memberikan posttest kepada ibu hamil. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 10 orang ibu hamil. Didapatkan hasil bahwa sebelum penyuluhan, sebagian besar ibu hamil memiliki kategori pengetahuan kurang yaitu sebanyak 10 orang (100%). Setelah dilakukan penyuluhan, sebagian besar ibu hamil memiliki kategori pengetahuan baik sebanyak 7 orang (70%). Kesimpulan, terjadi peningkatan pengetahuan ibu hamil mengenai manfaat akupresur P6 untuk mengatasi mual muntah pada ibu hamil. Diharapkan tenaga kesehatan meningkatkan edukasi kepada masayarakat, terutama ibu hamil mengenai manfaatkan akupresur sebagai metode non-framakologis dalam menurunkan mual muntah pada ibu hamil sehingga kesejahteraan ibu dan janin meningkat.